Metamorphoses of the African American Identity in Post-segregation Era and the Theory of Afrocentrism - D. M. BONDARENKO; N. E. KHOKHOLKOVA (Контуры глобальных трансформаций: политика, экономика, право, 2018)
The article deals with the issue of African American identity in the  post-segregation period (after 1968). The problem of African  Americans’ “double consciousness”, marked for the first time yet in  the late 19th – early 20th century, still remains relevant. It is that  descendants of slaves, who over the centuries have been relegated  to the periphery of the American society, have been experiencing and in part are experiencing an internal conflict, caused  by the presence of both American and African  components in their identities. The authors focus on Afrocentrism  (Afrocentricity) – a socio-cultural theory, proposed by Molefi Kete  Asante in 1980 as a strategy to overcome this conflict and to  construct a particular form of “African” collective identity of African  Americans. This theory, based on the idea of Africa and all people of  African descent’s centrality in world history and culture, was urged to  completely decolonize and transform African Americans’  consciousness. The Afrocentrists proposed African Americans to re- Africanize their self-consciousness, turn to African cultural roots in  order to get rid of a heritable inferiority complex formed by slavery and segregation. This article presents a brief outline of the  history of Afrocentrism, its intellectual sources and essential  structural elements, particularly Africology. The authors analyze the  concepts of racial identity, “black consciousness” and “black unity” in  the contexts of the Afrocentric theory and current social realities  of the African American community. Special attention is paid to the  methodology and practice of Afrocentric education. In Conclusion,  the authors evaluate the role and prospects of Afrocentrism among  African Americans in the context of general trends of their identities transformations.